Effect of melatonin on the oxidative metabolism of colostrum phagocytes of diabetic women - Calderon, Iracema de Mattos Paranhos [UNESP]; Morceli, G. [UNESP]; Hara, C.; Volpato, R.; Rudge, Marilza Vieira Cunha [UNESP]; Honorio-Franca, A.; Franca, E. (Monduzzi Editore S P A, 2011)
Aim: the aim of this study was verified the ability of melatonin hormone to modulate the oxidative metabolism of colostral phagocytes from diabetic mothers. Methods: based on 100g-OGTT and glucose profile analysis subjects were allocated into two groups: Non-diabetic (ND-10) and Diabetic (DM-8). Cells were separated by a Ficoll-Paque gradient and the oxidative metabolism was available thought superoxide release by colostrum phagocytes using the cytochrome C method. Results: melatonin hormone increased superoxide release by colostrum phagocytes of ND and decreased these release in colostrum phagocytes of DM mothers. Conclusion: the results suggest that the melatonin hormone can modulate the oxidative metabolism of phagocytes and an existence of relationship between control of glucose metabolism and melatonin action in colostrum phagocytes.
Keywords: Colostrum; phagocytes; superoxide; melatonin; diabetes